1998
DOI: 10.1172/jci1560
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase modulates angiogenesis in response to tissue ischemia.

Abstract: We tested the hypothesis that endothelial nitric oxide synthase (eNOS) modulates angiogenesis in two animal models in which therapeutic angiogenesis has been characterized as a compensatory response to tissue ischemia. We first administered L -arginine, previously shown to augment endogenous production of NO, to normal rabbits with operatively induced hindlimb ischemia. Angiogenesis in the ischemic hindlimb was significantly improved by dietary supplementation with L -arginine, compared to placebo-treated cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
891
5
18

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,125 publications
(967 citation statements)
references
References 51 publications
53
891
5
18
Order By: Relevance
“…26 Inhibitors of eNOS decrease VEGF-induced angiogenesis. 27,28 In addition, ischemia-induced angiogenesis is reduced in eNOS knockout mice, 29 and in rat models, oral folate can rescue this process in a NO-dependent manner. 30 eNOS production of NO depends on the cofactor BH 4 .…”
Section: Psma Expression In Tumor Neovasculaturementioning
confidence: 99%
“…26 Inhibitors of eNOS decrease VEGF-induced angiogenesis. 27,28 In addition, ischemia-induced angiogenesis is reduced in eNOS knockout mice, 29 and in rat models, oral folate can rescue this process in a NO-dependent manner. 30 eNOS production of NO depends on the cofactor BH 4 .…”
Section: Psma Expression In Tumor Neovasculaturementioning
confidence: 99%
“…48,49 As it was clearly demonstrated that laser Doppler flow velocity correlates well with the capillary density, 48,49 we measured the cardiac blood flow by means of a laser Doppler blood flow meter (Laser Doppler Image, Moor Instruments, Devon, UK). Indeed, we confirmed that the blood flow measured by LDI correlated well with the capillary den-sity (data not shown).…”
Section: Monitoring Cardiac Blood Flowmentioning
confidence: 99%
“…NO also modulates vascular permeability [6][7][8], angiogenesis [9,10], platelet adhesion and aggregation [11][12][13], and leukocyte adhesion [14][15][16]. Thus, NO bioavailabilty is important in maintaining several aspects of homeostasis and its dysfunction contributes to a large variety of diseased states [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%